Greed is dead politics after individualism - Collier, Paul. (London Allen Lane, 2020)
Throughout history, successful societies have created institutions which channel both competition and co-operation to achieve complex goals of general benefit. These institutions make the difference between societies that thrive and those paralyzed by discord, the difference between prosperous and poor economies. Such societies are pluralist but their pluralism is disciplined.
Includes bibliographical references and index.
Keywords: Individualism--Political aspects